Indonesian Realistic Mathematics Education: Alternative Mathematics Learning Approach to Improve Fifth Grade Numeracy Literacy Skills - Ekayanti, I Gusti Ayu Putu Wintari (Journal for Lesson and Learning Studies, 2024)
According to the findings of observations, students’ literacy numeracy skills are still considered to be weak. The findings of the computer-based national assessment show that fewer than 50% of pupils have attained the required level of ability. This study aims to analyze the impact of Indonesian realistic mathematics education on numeracy literacy skills of fifth grade students. The type of research used in this study is a quasi-experimental design with a non-equivalent control group design. The population of this study were all fifth-grade elementary school students as many as 123 people consisting of 8 classes contained in 8 public elementary schools. The entire population is equalized with a one-way ANOVA test after giving a pretest. If the entire population is declared equal, the sampling technique used is cluster random sampling. The data collection method was collected using a 3 questions description test, then the data was analyzed using descriptive statistical analysis techniques and inverential statistical analysis techniques with the Polled Variance T-Test. The result found that the Indonesian realistic mathematics education learning approach affects the Numeracy Literacy Skills of Fifth Grade Students by 52.9%. The findings of this study provide a theoretical foundation for applying the PMRI approach to mathematics instruction in elementary schools, with a focus on students’ numeracy literacy skills.